2018
DOI: 10.1080/14739879.2018.1531271
|View full text |Cite
|
Sign up to set email alerts
|

GPs and spiritual care: signed up or souled out? A quantitative analysis of GP trainers’ understanding and application of the concept of spirituality

Abstract: Background: GPs have a wide range of attitudes to spirituality which contribute to variations in the spiritual care they report to practice. Aim/Objective: To assess concepts of spirituality and their application in a sample of GPs trainers. To explore statistically the relationship between personal spiritual affiliation, attitudes to, and reported practice of, spiritual care. To examine whether GP trainers consider training in spiritual care to be adequate. Methods: Questionnaire: 87 GP trainers at a GP train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 15 publications
0
15
0
7
Order By: Relevance
“…More recently, there have been international efforts to improve spiritual care not only in palliative care, but in healthcare generally [10,11]. However, healthcare professionals still report difficulty in grasping what is meant by spirituality and spiritual care and hence often fail to meet the spiritual needs of patients [12][13][14]. This is a matter of concern as, according to the WHO, the spiritual dimension is an integral meaning-giving aspect of human existence and spiritual needs are commonly experienced by patients with sudden ill-health or loss, chronic conditions, and life-limiting conditions [15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, there have been international efforts to improve spiritual care not only in palliative care, but in healthcare generally [10,11]. However, healthcare professionals still report difficulty in grasping what is meant by spirituality and spiritual care and hence often fail to meet the spiritual needs of patients [12][13][14]. This is a matter of concern as, according to the WHO, the spiritual dimension is an integral meaning-giving aspect of human existence and spiritual needs are commonly experienced by patients with sudden ill-health or loss, chronic conditions, and life-limiting conditions [15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…They identified four categories of attitudes labelled as rejecting, guarded, pragmatic and embracing. 27 …”
Section: Methodsmentioning
confidence: 99%
“…26 Previous quantitative survey work with GP trainers in Scotland found that spirituality was perceived by educators as a meaningful, useful, but unclear concept. 27 Researchers investigating how spiritual health should be discussed in primary care have adopted a variety of definitions drawing themes from traditional religion through to humanism ( box 1 ). One of the most frequently adopted is a consensus definition from international holistic care conferences that encompasses all the concepts listed in box 1 , apart from inner peace, strength and resilience.…”
Section: Introductionmentioning
confidence: 99%
“…However, although professional guidance goes some way to outlining what is recommended it is becoming clear that although most GPs think that spirituality is meaningful and important to general practice, many are unclear about what this term means and feel inadequately trained when it comes to applying it (4).…”
mentioning
confidence: 99%